Phytochemistry and Pharmacological Property of Musa balbisiana Colla: A Mini-Review - Swargiary, Ananta; Boro, Harmonjit; Roy, Mritunjoy Kumar; Akram, Muhammad (Pharmacognosy Reviews)
Plants are known for rich medicinal values because of the presence of several secondary metabolites. Musa balbisiana Colla is an important plant native to India and many other Asian countries. Parts of this plant is known to contain rich medicinal and traditional values. The present study attempts to review the phytochemical and pharmacological properties of M. balbisiana. Literature survey was carried out using google, google scholar, pubmed, and other reliable resources. Several parts of the plant is known to contain many pharmacological properties such as antidiabetic, antibacterial, anticancer, hepatoprotective properties, etc. Of the several pharmacological properties, antibacterial and antidiabetic property of M. balbisiana was abundantly studied while other properties such as anticancer, contraceptive activity were less explored. Phytochemical studies have reported several secondary metabolits from the plant. M. balbisiana Colla has numerous phytochemicals and has a substantial pharmacological activity that can help to boost different health issues.
Keywords: Musa balbisiana Colla; Ethnomedicine; Phytochemicals; Bioactivity; Pharmacological property.